Managing separation in international purchasing and supply: A systematic review of literature from the resource-based view perspective - Harri Lorentz; Mukesh Kumar; Jagjit Singh Srai (Elsevier Ltd, 2022)
The aim of this research is to find out how the extant literature on international purchasing and supply management (PSM) covers the elements of capability from the perspective of distance. A priori, we form a framework of capability driving elements and conclude that distance—in its multiple dimensions—is the fundamental management aspect in international PSM. Equipped with analytical frameworks and a bottom–up process for identifying emergent themes, a systematic literature review was conducted on a representative sample of scholarly literature on international PSM, using the NVivo analysis software and a data display as tools. We identify several capability relevant themes from the literature, and provide a distance-based a posteriori conceptualisation of international PSM, founded in the information processing theory, with the source-user, user-user and source-source distance types driving the information processing requirements, and loading avoidance, policy-based and enhancement mechanisms determining the information processing capacity.